1995
DOI: 10.1161/01.cir.91.6.1749
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Sudden Cardiac Death in Middle-Aged British Men

Abstract: Three risk factors appear to be specific or particular to the risk of SCD, and these and other risk factors operate differently in patients with versus those without preexisting IHD. These findings have implications for the causes and prevention of SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
3
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 36 publications
4
131
3
10
Order By: Relevance
“…17) This means that the cause of sudden death was highly associated with arteriosclerosis. 18) In our study, sudden death occurred in 7 out of 21 deaths (33%) while the remaining 14 patients (67%) died of progressive heart failure. The serum cholesterol level in patients with CAD who died suddenly (n = 3) was greater than 250 mg/dL, while that in the patients without CAD who died suddenly (n = 4) was lower than 250 mg/dL.…”
Section: General Findingsmentioning
confidence: 46%
“…17) This means that the cause of sudden death was highly associated with arteriosclerosis. 18) In our study, sudden death occurred in 7 out of 21 deaths (33%) while the remaining 14 patients (67%) died of progressive heart failure. The serum cholesterol level in patients with CAD who died suddenly (n = 3) was greater than 250 mg/dL, while that in the patients without CAD who died suddenly (n = 4) was lower than 250 mg/dL.…”
Section: General Findingsmentioning
confidence: 46%
“…[17][18][19] Previous history of angina, MI, or hypertension was predictive of arrhythmic mortality at 2-year follow-up in our preselected patients; this is consistent with previous findings. 20 Three main factors, left ventricular dysfunction, ischemia, and electrical instability are involved in the genesis of arrhythmic death. 21 Thus, while previous MI and left ventricular dysfunction form the substrates, ischemia and ventricular premature beats provide the triggers for ventricular arrhythmia, which in turn increases the risk of mortality and sudden death after MI.…”
Section: Mechanistic Link Between Demographic and Clinical Variables mentioning
confidence: 99%
“…Высокая ЧСС в покое может от-ражать повышенную активность симпатической и/или сни-женную активность парасимпатической нервной системы [8]. ЧСС более 80-85 уд/мин в состоянии покоя связана с рис-ком развития артериальной гипертонии (АГ), атеросклероза и является независимым предиктором ССО как у лиц без симптомов ССЗ, так и с наличием таковых [9][10][11][12][13][14]. Aronow W. и соавт.…”
Section: Methodsunclassified
“…Accelerated resting heart rate (HR) can reflect an increased activity of sympathetic and/or decreased activity of parasympathetic nervous system [8]. Resting HR over 80-85 beats per min is associated with a risk of arterial hypertension (AH) and atherosclerosis development and is an independent predictor of CVE in subjects with and without CVD symptoms [9][10][11][12][13][14]. Aronow W. et al have revealed relation between cardiovascular mortality and HR recorded during 24 h Holter ECG monitoring (24-h ECG) [15].…”
Section: High Hr Is a Potential Cardiovascular Risk Factor In Rheumatmentioning
confidence: 99%